Low omega‐3 polyunsaturated fatty acids predict reduced response to standard antidepressants in patients with major depressive disorder. Issue 5 (31st March 2022) - Cussotto, Sofia; Delgado, Inês; Oriolo, Giovanni; Kemper, Jonas; Begarie, Diane; Dexpert, Sandra; Sauvant, Julie; Leboyer, Marion; Aouizerate, Bruno; Martin‐Santos, Rocío; Schaefer, Martin; Capuron, Lucile
Abstract: Background: Major depressive disorder (MDD) is characterized by a high rate of treatment resistance. Omega (ω)−3 polyunsaturated fatty acids (PUFAs) were shown to correlate with depressive phenotype both in rodents and in humans. However, few studies to date have investigated the role of PUFAs in antidepressant response. The primary aim of this study was to assess the link between baseline PUFA composition and changes in depressive symptoms as well as antidepressant response in a multicenter study of depressed patients. Methods: Sixty depressed adults who met criteria for MDD according to DSM‐IV‐TR were recruited. Neuropsychiatric evaluations occurred at baseline and after 4 and 8 weeks of treatment with standard antidepressants, including escitalopram ( N = 45), sertraline ( N = 13) and venlafaxine ( N = 2). At study endpoint, patients were stratified into responders (R) or non‐responders (NR) based on their MADRS (Montgomery‐Åsberg Depression Rating Scale) score. Baseline PUFA levels were assessed and their association with clinical response was determined. Results: Lower ω−3 PUFA levels were associated to worse baseline symptomatology. Baseline levels of PUFAs were significantly different between R and NR, with R exhibiting lower docosahexaenoic acid (DHA), eicosapentaenoic acid (EPA) and ω−3 index; and higher ω‐6/ω−3 ratio than NR before the start of antidepressant treatment. DHA levels as well as the ω−3 index and ω‐6/ω−3 ratio significantly predicted response to antidepressants at study endpoint. Conclusions: These results show that baseline levels of PUFAs predict later response to standard antidepressants in depressed subjects. They suggest that PUFA intake and/or metabolism represent a novel modifiable tool for the management of unresponsive depressed patients.